Strengthening Families: Nurturing and Attachment - David C. Diehl; Jessica N. Wente; Larry F. Forthun (EDIS)
While nurturing comes naturally for many parents, it can be helpful to think about the concrete ways in which parents can strengthen their bonds with their children. This 3-page fact sheet offers some ideas of things that you can do to help foster nurturing and attachment between you and your child. Written by David C. Diehl, Jessica N. Wente, and Larry F. Forthun, and published by the UF Department of Family Youth and Community Sciences, December 2011.